Construção do SUAS em pequenos municípios do sudoeste paulista: o caso de seis cidades vizinhas - Duarte, Fabiana Giannetti (2020)
The main objective of this dissertation is characterizing the ways of presence and consolidation of the Social Work System - SUAS (Sistema Único de Assistência Social) at Taquarituba (Saint Paul, Brazil) and at the neighbor cities of small size I and II: Taguai, Tejupa, Itai, Coronel Macedo and Fartura until 2015 and their eventual alterations in the period between 2016 and 2019. The specific objectives of the research are: a) analyzing the rhythm and the characteristics of the implementation of LOAS (Law of Social Work) and SUAS between 1993 and 2015 in each city under analysis and comparing them; b) identifying the alterations occurred in the last 4 years (2016-2019). The research has been developed with the participation of five City Managers of Social Work and five workers of SUAS in four cities of small size I and two cities of small size II. The research used qualitative approach and the data collection tool were interviews with open questions pursuing knowing the dynamics of implementation of services, programs, projects, benefits, ways of influence of National Policy of Social Work – PNAS (Política Nacional de Assistência Social) and of regulation of SUAS in local management and main challenges for its operation and management. We verified that the presence of local factors causes several responses in the implementation of SUAS in cities of small sizes I and II in Saint Paul State, where the impact of the federal norm to the city constitution of SUAS presents different rhythm and expressions as well as different grades of local consistency in the institutionalization of SUAS, being the inter-cities relationships limited in the territory development of SUAS. These results allowed us to discuss the construction and destruction of SUAS found in the discourse of interviewee